2011
DOI: 10.1007/s11104-011-0818-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in soil biochemical properties associated with Ligularia virgaurea spreading in grazed alpine meadows

Abstract: Ligularia virgaurea, a toxic perennial weed, has become a dominant species in the heavilygrazed alpine meadows of the eastern Qinghai-Tibetan Plateau over recent decades. We investigated changes in soil biochemical properties associated with L. virgaurea spreading in grazed alpine meadows at three sites. Soil and root biomass samples were taken at depths of 0-8 cm, 8-16 cm and 16-24 cm from patches where L. virgaurea was dominant and from areas between L. virgaurea patches, with only other native species. Acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…Shi et al . found that L. virgaurea appeared mostly in extremely degraded grassland and could increase the N mineralization and N concentration of top soil in the alpine meadow on the Tibetan Plateau37, which support our result that L. virgaurea is N stress tolerant. The growth of S. officinalis was not affected by N addition (except its leaf length was elongated by increased N when neighbours were retained), implying that N might not be the main limiting factor for this species in our experimental site, and this species could be classified as having intermediate N sensitivity.…”
Section: Discussionsupporting
confidence: 90%
“…Shi et al . found that L. virgaurea appeared mostly in extremely degraded grassland and could increase the N mineralization and N concentration of top soil in the alpine meadow on the Tibetan Plateau37, which support our result that L. virgaurea is N stress tolerant. The growth of S. officinalis was not affected by N addition (except its leaf length was elongated by increased N when neighbours were retained), implying that N might not be the main limiting factor for this species in our experimental site, and this species could be classified as having intermediate N sensitivity.…”
Section: Discussionsupporting
confidence: 90%
“…Soils are classified as alpine meadow soils according to the Chinese soil classification system (Institute of Soil Science, ). The surface 0–16 cm soil layer has a pH of 6.7 and contains 5.8% organic C, .0.41 g/kg N (with 4 mg/kg NH4+ and 13.5 mg/kg NO3 ) and total P of 1.0 g/kg (Shi, Li, Wu, Yang, & Long, ). Above‐ground litter dry‐matter production averaged 505 g m −2 year −1 , comprising approximately 0.78 leaf, 0.16 stem and 0.06 reproductive parts.…”
Section: Methodsmentioning
confidence: 99%
“…These findings agree with many previous studies showing that the AM fungal communities were determined by both plant communities [65] and some environmental factors [13], [14], and highlight the importance of deterministic process based on niche differentiation in driving the community assembly of AM fungi. In fact, changes of plant community and soil properties in this study should be ultimately attributed to the spreading of L. virgaurea , because its spreading could suppress the seedling recruitment of neighborhood plants by allelochemicals [36] as well as change soil characteristics via changing the activities of soil enzymes [66]. Further studies are encouraged to address how L. virgaurea spreading directly and indirectly regulates the AM fungal assemblages in alpine meadow ecosystems.…”
Section: Discussionmentioning
confidence: 91%